STАGES ОF DEVELОPMENT ОF THE INSURАNCE INDUSTRY IN UZBEKISTАN - Kenjayev Ilhom Giyozovich (Web of Journals Publishing, 2024)
This article provides proposals and recommendations related to the insurance services implemented in the national insurance market of Uzbekistan in recent years and their improvement.
Keywords: Insurer, insured, reinsurer, insurance services, insurance premium, insurance money, insurer's investment activity, insurance liability.